In vitro experience of human natural killer cell culture with feeder cells - Yu. V. Gelm; I. A. Pasova; L. Yu. Grivtsova; T. V. Konstantinova; N. V. Mikhaylovsky; V. A. Rybachuk; E. V. Abakushina; S. A. Ivanov; A. D. Kaprin (Медицинская иммунология, 2022)
Adoptive immunotherapy using NK cells has become a promising therapeutic area. NK cells are a component of the innate immune system, act as key regulators, and have potent antitumor cytolytic activity. In order to be able to evaluate the therapeutic effect of adoptive NK cell immunotherapy at preclinical stages, there is a need for reliable protocols for in vitro production of NK cells. There are a large number of publications on methods for activating and generating human NK cells, including using feeder-cells and various cytokines. The article describes the experience of cultivation of NK cells from cancer patients or donors with feedercells and without feeder-cells (control group). The K562 cell line was used as a feeder after irradiation of two types: after gene modification of K562 (gmK562) with membrane-bound mbIL15, mbIL21 and without it. NK cells donors and cancer patients were mixed with K562 in a ratio of 1:1, 1:2 and 1:5 on 0, 7 and 14 days respectively. Daily morphological assessment showed that, NK cells donors and cancer patients began to proliferate and increase in size, while the viability of feeder cells began to decrease after 3 days of cultivation, and they were less than 20% on 21 days. NK cells of donors and cancer patients went into apoptosis, their viability level decreased to 70% in the control group (without feeder-cells) after 3 days of cultivation. A comparative evaluation of two different methods of obtaining human NK cells was carried out. It was shown when NK cells were isolated by magnetic selection, the proportion of CD3-CD56+CD16+ cells were more than 90%, and after the removal of adherent cells, it was at least 60%. When cultivating NK cells cancer patients (after magnetic separation) together with gmK562 on the 21st day, it was possible to increase the number of NK cells up to 85 times. When cultivating NK cells donors (after adhesion) together with non-genetically modified K562 cells on 21 days, it was possible to increase the number of NK cells up to 8 times. It was shown that in the supernatants collected during the cultivation of NK cells with feeder cells (both irradiated with K562 and genetically modified with K562), the concentrations of TNFα and IFNγ increased many times relative to the control group. The optimal conditions for culturing NK cells were experimentally selected to obtain a large number of NK cells.